2012
DOI: 10.1258/phleb.2011.011051
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of hypoxia-inducible factor-1α and metallothionein in varicocele and varicose veins

Abstract: Our results revealed the higher expression of HIF-1α and MT in varicocele and varicose veins than in the control group; MT overexpression in the muscle layer of both diseased vessels and especially located in the endothelium under confocal microscopy. MT has the function to protect vascular cells from apoptosis under hypoxia. Thus, this MT function may cause a decreased vascular cell apoptosis and then contribute to the dilated and thickened walls of varicocele and varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Lee et al . suggested higher expression of hypoxia‐inducible factor 1‐α and metallothionein in varicocele and varicose veins than in the control group, which might decrease vascular wall apoptosis and contribute to the dilation of veins . However, Yazici et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lee et al . suggested higher expression of hypoxia‐inducible factor 1‐α and metallothionein in varicocele and varicose veins than in the control group, which might decrease vascular wall apoptosis and contribute to the dilation of veins . However, Yazici et al .…”
Section: Discussionmentioning
confidence: 94%
“…14 Lee et al suggested higher expression of hypoxia-inducible factor 1-a and metallothionein in varicocele and varicose veins than in the control group, which might decrease vascular wall apoptosis and contribute to the dilation of veins. 15 However, Yazici et al reported that varicocele might not be attributable to a systemic vascular insufficiency, and is not significantly related to varicose veins. 9 In addition, Sakamoto et al suggested that patients with bilateral varicocele might have a higher chance of being associated with venous abnormalities than those with unilateral varicocele.…”
Section: Discussionmentioning
confidence: 99%
“…Specific markers of hypoxia found in varicocele include hypoxia inducible factor 1 alpha (HIF-1a), vascular endothelial growth factor, and adrenomedullin (ADM). Several studies have examined the expression of HIF-a in internal spermatic vein tissue samples obtained during adult varicocelectomy and confirmed a dramatic up-regulation compared to controls [14,15]. Hu and colleagues compared fertile and infertile adults with varicocele by sampling the internal spermatic vein (ISV) and brachial vein for levels of HIF-1a and ADM [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many molecules from many different pathways are involved in the pathological processes associated with varicose veins. These molecules include hypoxia-inducible factor 1-alpha (HIF-1alpha) in the hypoxia pathway [7], the Janus kinase/signal transducers and activators of transcription (JAK-STAT) and nuclear factor kappaB (NF-kappaB) in the inflammatory pathway [8], poly ADP ribose polymerase (PARP) and bax in the apoptotic pathway [9], adhesion molecules and cytokines such as intercellular adhesion molecule 1 (ICAM-1), interleukin-1 alpha (IL-1alpha), and tumor necrosis factor alpha (TNF-alpha) [10]. However, these molecules account for only some of the tangled mechanisms, and many more remain to be identified.…”
Section: Introductionmentioning
confidence: 99%